Analysis of Workforce Requirements Based on Production Capacity and Work Time Utilization to Improve Operational Efficiency at PT XYZ - Cantika Agusta Sari Ratna Dewi; Jaka Purnama (Telkom University, 2026)
The rapid development of the industrial sector requires manufacturing companies to manage resources effectively and efficiently, particularly in workforce allocation and working time utilization, in order to maintain productivity and operational performance. This study was conducted at PT XYZ, a stove manufacturing company, with the aim of analyzing employee workload, evaluating the utilization of working time, and determining the optimal number of workers based on production capacity requirements. Based on preliminary observations, several production divisions were found to experience ineffective working time utilization, resulting in workload imbalances and less optimal operational efficiency. This study applies the Workload Analysis (WLA) method supported by stopwatch time study measurements and the Cardiovascular Load (CVL) method to assess both operational and physical workload conditions. The collected data include work element times, number of workers, production output, non-productive time, and workers’ heart rate measurements. The data were processed through normal time and standard time calculations, performance rating determination, allowance calculations, workload analysis, and workforce requirement evaluation. The results show that all workers were classified within the light workload category based on CVL values below 30%, indicating that the physical workload remained within acceptable limits. Furthermore, the WLA results revealed imbalances in several production divisions, particularly welding and assembly, which required workforce adjustments to improve workload distribution and operational efficiency. By implementing appropriate workload management, the company is expected to reduce ineffective working time, improve labor productivity, and enhance overall operational efficiency.